Achieving smooth motion of stick–slip piezoelectric actuator by means of alternate stepping. (1st December 2022) - Ding, Zhaochen; Dong, Jingshi; Zhou, Xiaoqin; Xu, Zhi; Qiu, Wen; Shen, Chuanliang
Graphical abstract: Highlights: The designed actuator can achieve smooth motion under no-load and load conditions. The switching of different stepping characteristics is performed by controlling the voltage. The output performance is relatively stable when the pre-tightening deformation is between 50 µm and 200 µm. Abstract: Piezoelectric actuators are widely used in various precision instruments owing to their rapid response, high motion accuracy, and immunity to electromagnetic interference. However, achieving smooth motion with a load is difficult when using existing piezoelectric actuators because of their unique driving principle, which limits their application. To achieve smooth motion with a load, a stick–slip piezoelectric actuator using the alternating stepping method was proposed in this study. The two driving feet collaborate to push the slider through a single piezoelectric stack. After considering the structure and working principle of the actuator, a feasibility analysis was performed. Subsequently, the pseudo-rigid-body method, elastic beam method, and finite element method were applied to calculate the displacement relationship of the flexure hinge mechanism. Finally, the prototypes were processed to evaluate their output performance. The comparative experiments explain the role of driving feet-A and B and demonstrate that biped synergy can achieve smooth motion. The subsequent test results show that the designed actuator has exceptionally high adaptability, and the output performance is relatively stable when the pre-tightening deformation is between 50 µm and 200 µm. Most importantly, the designed actuator has good smoothness under no-load and horizontal load conditions, and the maximum speed and resolution are 24.42 mm/s and 0.80 µm, respectively. This is conducive to broadening the application range of piezoelectric actuators.